Magnetization of low grade iron ore using empty fruit bunch ash - Yunus, Nurul Azhani; Ani, Mohd Hanafi; Purwanto, Hadi; Mohd. Salleh, Hamzah; Zamani Abd Rashid, Rusila; Akiyama, Tomohiro (Trans Tech Publications, Switzerland, 2013)
Malaysian low grade iron ore is unsuitable as raw material for domestic iron making due to high energy consumption which correspond to low iron content. The present agricultural residues from domestic palm oil industry are attractive proposition as energy source for iron making. This work describes the use of ash produced from pyrolysis of palm oil Empty Fruit Bunch (EFB) to magnetize the low grade iron ore. A briquette composite of iron ore and ash is subjected to reduction process using an electric tube furnace under argon atmosphere at 873K and 1073K. The ore was successfully magnetized through reduction process as carbon in EFB ash act as reductant. The results showed that the reduction degree was greatly enhanced with increasing of temperature and time. The significant phase changes of iron ore from a non-magnetic material of goethite to a strong magnetic material of magnetite was detected in XRD patterns. The process indicated that substitution of coal with EFB ash as an energy source has a potential in replacing fossil fuel by magnetizining the iron ore as well as encourage waste management control.